Development of preheating methodology for a 5 kW HT-PEMFC system. (26th October 2021) - Choi, Mingoo; Kim, Minjin; Sohn, Young-Jun; Kim, Seung-Gon
Abstract: Compared to the low-temperature proton exchange membrane fuel cell (LT-PEMFC) system, the high-temperature proton exchange membrane fuel cell (HT-PEMFC) system has a simple balance of plant (BOP) configuration and high heat recovery efficiency. However, to commercialize this system, the start-up time should be shortened. This study aims to develop a preheating methodology for the 5 kW HT-PEMFC system, which is the target system. The entire start-up time of this system is dominated by the warm-up time of the stack among various other system components. An advanced preheating method was experimentally verified by combining three heating methods of the stack: coolant heating, reaction heating, and air heating. Additionally, considering the power consumption of the target system, a method to reduce the warm-up time was proposed. Ultimately, we found that the combined coolant and reaction heating method was the best. Furthermore, a case study revealed that using an oil heater with variable heating capacity on the target system can reduce the start-up time by 23% compared to a fixed capacity heater. Highlights: An effective preheating method for a HT-PEMFC stack was verified experimentally. An operation algorithm was established for the 5 kW HT-PEMFC system. The start-up time of the system was reduced based on power consumption.